2023
DOI: 10.1063/5.0152262
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of thermal enhancement using MoS2–Ag/C2H6O2 in Prandtl fluid with Soret and Dufour effects across a vertical sheet

Abstract: Due to numerous applications, the study of hybrid nanofluids is a hot topic of research, which enables us to improve thermal performance. The current work is carried out to inspect thermal and solutal transportation in the Prandtl model toward a heated stretched plate. The flow analysis has been developed in Cartesian coordinates considering variable thermal conductivity and non-uniform diffusion coefficient. Furthermore, the modeling of physical phenomena is carried out considering the porous stretched surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Elboughdiri et al 16 explored the solar applications with significant thermal outcomes due to nanofluid accounted by cone. The Dufour impact in Prandtl number fluid flow via vertically moving surface was reported by Liu et al 17 . Waqas et al 18 endorsed the nanofluid properties through porous channel with radiated impact.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Elboughdiri et al 16 explored the solar applications with significant thermal outcomes due to nanofluid accounted by cone. The Dufour impact in Prandtl number fluid flow via vertically moving surface was reported by Liu et al 17 . Waqas et al 18 endorsed the nanofluid properties through porous channel with radiated impact.…”
Section: Introductionmentioning
confidence: 79%
“…In view of above governing equations, the boundary layer equations for current model are expressed as 16 , 17 : …”
Section: Problem Statementmentioning
confidence: 99%
“…Similarly, Imran et al 44 reported the Ellis fluid over flexible framework with entropu generation. Liu et al 45 gave numerical results for hybrid nanofluid over vertical channel with sorect influence.…”
Section: Introductionmentioning
confidence: 99%